Performance of Subsurface Flow Constructed Wetland Systems in the Treatment of Al-Rustumia Municipal Wastewater using Continuous Loading Feed - A. Rahi, Muna; A. H. Faisal, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
This study aimed at comparing the performance of vertical, horizontal and hybrid subsurface flow systems in secondary treatment for the effluent wastewater from the primary basins at Al-Rustumia wastewater treatment plant, Baghdad, Iraq. The treatments were monitored for six weeks while the testsduration were from 4 to 12 September 2018 under continuous wastewater feeding for chemical oxygen demand (COD), total suspended solid (TSS),ammonia-nitrogen(NH4-N) and phosphate (PO4-P) in comparison with FAO and USEPA standards for effluent discharge to evaluate the suitability of treated water for irrigation purposes. Among the systems planted with Phragmites Australia, the hybrid subsurface flow system which consisted of vertical unit followed by horizontal one, considerably removed the pollutants more efficiently than the single operated systems. The planted hybrid subsurface flow wetland system was achieved the highest removal with a mean removal rate of COD,TSS, NH4-N, and PO4-Pat 99.3, 83.2,67.4 and 53% respectively and these percentages were decreased in the other systems. The results proved that the planted vertical subsurface flow unit can be removed the COD, TSS, NH4-N and PO4-Pwith values of 93, 71.1, 43.3 and 30.7%, respectively while the achieved removals by horizontal subsurface flow unit of 99, 74.3, 54.5 and 20.3%, respectively. The planted horizontal subsurface flow wetland, however, showed a good efficacy for all parameters in the treatment process except for PO4-P when it is compared with vertical system, however, there is a clear increase in the NO3-N effluent concentration for all treatment units.